Tunable Self-Assembly of Diblock Copolymers into Colloidal Particles with Triply Periodic Minimal Surfaces - Lin, Zhixing; Liu, Shaohua; Mao, Wenting; Tian, Hao; Wang, Nan; Zhang, Ninghe; Tian, Feng; Han, Lu; Feng, Xinliang; Mai, Yiyong (Angewandte Chemie International Edition, 2017)
We herein report the tunable self-assembly of simple block copolymers, namely polystyrene-block-poly(ethylene oxide) (PS-b-PEO) diblock copolymers, into porous cubosomes with inverse (Formula presented.) or (Formula presented.) mesophases of controlled unit cell parameters as well as hexasomes with an inverse hexagonal (p6mm) structure, which have been rarely observed in polymer self-assembly. A new morphological phase diagram was constructed for the solution self-assembly of PS-b-PEO based on the volume fraction of the PS block against the initial copolymer concentration. The formation mechanisms of the cubosomes and hexasomes have also been revealed. This study not only affords a simple system for the controllable preparation and fundamental studies of ordered bicontinuous structures, but also opens up a new avenue towards porous architectures with highly ordered pores.
CRIS-Team Scopus Importer:2023-03-20
Keywords: block copolymers; colloidal particles; inverse mesophases; phase diagrams; self-assembly